Occult Celiac Disease Associated with Lymphocytic Sclerosing Cholangitis - Hugh J Freeman; WC Peter Kwan (Canadian Journal of Gastroenterology)
A 60-year-old male with dermatitis herpetiformis and a previously treated lymphoma involving an inguinal lymph node developed abnormal liver chemistry tests. Because of intermittent diarrhea, additional studies revealed lymphocytic colitis and occult celiac disease that responded to a gluten-free diet. A liver biopsy done to explore persistently abnormal liver chemistry tests showed a portal tract-centred inflammatory process characterized by biliary ductal proliferation, epithelial lymphocytosis and concentric lamellar fibrosis. Quantitation of immunoglobulins was normal and antimitochondrial antibodies were negative. Retrograde cholangiograms showed radiological features typical of primary sclerosing cholangius. The epithelial lymphocycosis reported in gastric, small and large intestinal mucosa of some patients with celiac disease may also be present in the biliary ductal columnar epithelium. This report provides additional evidence that celiac disease may be a far more extensive pathological process.